Protective effect of Saussurea involucrata polysaccharide against skin dryness induced by ultraviolet radiation - Wang, Lusheng; Yang, Kaiye; Jing, Rongrong; Zhao, Wengang; Guo, Keke; Hu, Zhenlin; Liu, Guangrong; Xu, Nuo; Zhao, Jungang; Lin, Li; Gao, Shuang (Frontiers in Pharmacology, 2023)
Exposure to ultraviolet B (UVB) radiation can damage the epidermis barrier function and eventually result in skin dryness. At present, most of the research on skin problems caused by UVB is focusing on issues such as photodamage and photoaging, with little work being devoted to skin dryness. Therefore, the search for active ingredients that can protect the skin against UVB-induced dryness will have scientific significance. Saussurea involucrata polysaccharide (SIP) has been shown to have significant antioxidant and anti-photodamage effects on the skin following UVB irradiation, but whether it can protect against skin dryness caused by UVB has not been reported. The purpose of this study was to investigate the protective effect of SIP against UVB-induced skin dryness by application of SIP-containing hydrogel in mouse model and to explore the underlying mechanisms of such effect by HaCaT cells. SIP was found to lower UVB-induced oxidative stress and DNA damage while increasing keratinocyte differentiation and lipid production in the epidermis to help repair epidermal barrier function, this would eventually be preventing skin dryness. The western blot analysis of UVB-irradiated skin tissue revealed a significant increase in peroxisome proliferator-activated receptor-α (PPAR-α) levels, indicating that the underlying mechanism might be related to the activation of PPAR-α signaling pathway. These findings could provide candidate active ingredients with relatively clear mechanistic actions for the development of skin sunscreen moisturizers.